A Distributed Algorithm for Topology Control in VANETs: Distributed Distant Node Graphical Structure (DDGST) Algorithm (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
Vehicle ad hoc networks—a subset of MANETs—allow cars to directly connect. These networks are independent of previous infrastructure. VANETs promote traffic safety, efficiency, and ITS application development. Their link allows this. Vehicular Ad-hoc Networks (VANETs) have grown in popularity due to its ability to efficiently and reliably connect automobiles. Vehicular networks evolve rapidly, making network topology maintenance problematic. VANET topologies are managed decentralized here. The algorithm uses neighbor numbers and distances to calculate vehicle transmission range. Simulations indicate that the suggested method reduces network partitions and maximizes connection. Due to the great mobility of VANET vehicles, the network architecture changes quickly. As this network topology is continually changing, creating strong and effective routing protocols is difficult. Topology control can overcome this difficulty. We present a distributed topology control mechanism that keeps VANETs online, reduces control messages, and prevents collisions. Node centrality and network density are used to fine-tune each node's transmission power. Computer simulations compare the proposed approach to different topology control algorithms. The results show that the suggested method outperforms the alternatives in network connectivity, longevity, and control overhead.